Bullying behavior and accumulated physical activity in Brazilian schooled adolescents (Research, Society and Development, 2020)
The present study aims to assess the association between bullying behavior, sociodemographic variables, and accumulated physical activity in Brazilian school children. This is a study with secondary data, using data from PeNSE 2015 Sample 2 (n = 10926). Binary logistic regression was used for data analysis to estimate the chance of occurrence of the phenomenon of bullying in the form of brute and adjusted Odds Ratio (OR). To verify the factors associated with bullying in Brazilian adolescents, the sample was stratified into "active" and "insufficiently active" in order to understand the behavior of bullying between each stratum. It was observed that males had twice as many chances (OR = 1.99; 95%CI 1.80 - 2.19) to present this bullying behavior when compared to females. It was found for the "active" stratum, an association between perpetrating bullying and males (OR = 2.21; 95%CI 1.82 - 2.67) and suffering bullying as self-perception (OR = 2.45; 95%CI 2.05 - 2.93). For the "insufficiently active", an association was noticed in the adjusted model between "perpetrating bullying" and males (OR = 1.88; 95%CI 1.65 - 2.13). It was noted that male adolescents who were bullied were more likely to be bullied. The results also suggest that in both the "active" and "insufficiently active" groups, those who perpetrate bullying are more likely to have been bullied, suggesting that the behavior of bullying is prior to physical activity.